Implementation of AI-Based Digital Platform Through Canva Application in Indonesian Language Subject for Students of SMP Negeri 15 Manado - Wijaya, Pratiwi Wardini Putri; Ratu, Donald M.; Iroth, Santje (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This study aims to explore the application of the Canva application in Indonesian language learning at SMP Negeri 15 Manado, especially in creating poster designs by grade VII students. Through a descriptive qualitative approach, this study involved observation, interviews, and documentation to analyze the effectiveness of Canva as a learning medium. The results showed that the majority of students were able to convey messages well through the posters they made, with many of them getting the predicate